2010
DOI: 10.1186/1754-6834-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Access to cellulose limits the efficiency of enzymatic hydrolysis: the role of amorphogenesis

Abstract: The efficient enzymatic saccharification of cellulose at low cellulase (protein) loadings continues to be a challenge for commercialization of a process for bioconversion of lignocellulose to ethanol. Currently, effective pretreatment followed by high enzyme loading is needed to overcome several substrate and enzyme factors that limit rapid and complete hydrolysis of the cellulosic fraction of biomass substrates. One of the major barriers faced by cellulase enzymes is their limited access to much of the cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
344
1
15

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 503 publications
(369 citation statements)
references
References 79 publications
9
344
1
15
Order By: Relevance
“…Recent work has demonstrated that rapid fiber fragmentation at the very early stages of hydrolysis leads to a dramatic reduction in slurry viscosity, which alleviates some of the issues associated with high solids hydrolysis (2). It has been suggested that fiber fragmentation is primarily induced by the endoglucanase family of enzymes (3,4), although other proteins present in the cellulolytic mixture, such as the more recently characterized oxidative enzymes (5,6) and amorphogenesis-inducing proteins (7)(8)(9), have also been shown to contribute to the overall deconstruction process.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work has demonstrated that rapid fiber fragmentation at the very early stages of hydrolysis leads to a dramatic reduction in slurry viscosity, which alleviates some of the issues associated with high solids hydrolysis (2). It has been suggested that fiber fragmentation is primarily induced by the endoglucanase family of enzymes (3,4), although other proteins present in the cellulolytic mixture, such as the more recently characterized oxidative enzymes (5,6) and amorphogenesis-inducing proteins (7)(8)(9), have also been shown to contribute to the overall deconstruction process.…”
mentioning
confidence: 99%
“…These disruptive proteins include examples from plants (Expansins) (13), bacteria (Expansin-like proteins (14,15) and some carbohydrate binding modules (CBMs) 2 (16)), and fungi * This work was supported by the Natural Sciences and Engineering Council (Swollenin (8,9,12), Loosenin (17), and CBMs (18)). These proteins have also been shown to promote a variety of disruptive effects on cellulosic biomass, including filter paper dispersion, crystallinity reduction, particle size reduction, swelling of cotton fibers, and roughening of cotton fiber surface (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The lignin sheath limits the accessibility of the enzymes to the cellulose. For lignin, its physicochemical features of low molecular weight and hydrophobicity restrict the swelling of cellulose and, therefore, negatively affect the accessible surface area (Donohoe et al 2008;Arantes and Saddler 2010). Additionally, cellulase can be irreversibly adsorbed on lignin via hydrophobic interactions, ionic bond interactions, and hydrogen bond interactions, consequently reducing the efficiency of saccharification.…”
Section: Introductionmentioning
confidence: 99%